Obozowa autobiografia Bogdana Bartnikowskiego. Świadectwo chłopca, który przeżył Auschwitz = Bogdan Bartnikowski`s camp autobiography. A testimony of the boy who survived Auschwitz) - Buganik, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A book of Bogdan Bartnikowski`s: "Dzieciństwo w pasiakach" [trans. Childhood in striped uniforms] portrays an experience of Auschwitz described from child`s perspective. These gulag reports can truly be called an autobiography. The author of this article, guided by the Philipe Lejeune`s definition of autobiography puts forward this thesis and proves that Bartnikowski`s memories are an actual autobiography. Additionally, he presents the very essence of the message, focusing primarily on the goals Bartnikowski chose while writing his book, that is namely - testimony, education and remembrance of the survivors and those who didn`t survive.
Keywords: Auschwitz-Birkenau Concentration Camp; autobiografia; Bartnikowski, Bogdan (1932- ); dziecko; obóz; świadectwo; wspomnienia; autobiography; child; camp; testimony; memories